Performance Investigation of DP-16QAM Ultra-wideband- Wavelength-Division Multiplexing Communication System: Optimum Power Consideration - Arwa Moosa; Raad Sami Fyath (مجلة النهرين للعلوم الهندسية, 2023)
Recently, there is increasing interest in using the 18 THz bandwidth offered by S+C+L band to increase the transmission capacity of fiber communication systems. This leads to the generation of ultra-wideband (UWB) wavelength-division multiplexing (WDM) optical communication systems. In these advanced systems, stimulated Raman scattering (SRS) causes a power transfer from high-frequency channels to low-frequency channels. This effect leads to an increase in the nonlinear interference (NLI) between the UWB-WDM channels. Power optimization techniques are required to balance transfer power between band channels, thus increasing the maximum transmission reach (MTR) along with increasing system capacity. In this paper, the transmission performance of S+C+L band system operating with dual-polarization 16-QAM signaling is investigated using enhanced Gaussian noise model. The transmitter and receiver for each DP channel use a -polarized laser and incorporate two identical configurations, one for x- and the other for y-state of polarization (SOP). The results are presented for two values of symbol rate, 40 and 80 GBaud, where the system carries 360 (=160+80+120) and 180 (=80+40+60) channels, respectively. The results revel that the MTR of both cases is equal to 12 100 km-spans when the channel lunch power equals to -4 and -2 dBm, respectively. This work also shows the effect of NLI components as a function of the number of spans, channel spacing, and channel launch power. The results show that the cross-phase modulation component of the NLI has high accumulated value with transmission distance, while the self-phase modulation component is almost constant.